Productive capacity of Dipteryx odorata (Aubl.) Willd. in an integrated livestock production system in the Lower Amazon, Brazil - da Silva Lameira , Mahyanny Karoline (2022)
The forest component's growth and production are important to asses the technical feasibility of an integrated livestock production system (iLPF) with native species from the Amazon. The objective of this work was to analyze and select hypsometric and volumetric equations for Dipteryx odorata and analyze its silvicultural development in an iLPF system in the Lower Amazon. Data were collected in the municipality of Mojuí dos Campos, Pará, using dendrometric and qualitative variables from 240 cumaru trees in a 1ha plantation with 9 years of implantation, in a spacing of 5 m x 7 m. Six hypsometric models and nine volumetric models were adjusted. To select each equation, the following criteria were observed: adjusted coefficient of determination (R²aj) standard error of the estimate in percentage (Sxy%) mean percentage deviation (DMP), the significance of the parameters by the t-test, normality of the residuals by the Kolmogorov- Test Smirnov and graphical analysis of percentage residuals. The simple linear model was the most suitable for estimating the volume's total height and the Husch model.